Student personal organizer assistant / Mohammad Razi Abdul Hak - Abdul Hak, Mohammad Razi (1997)
Most students tend to be in trouble when they try to get themselves organized. It would be of a great help if they have a personal assistant for this job, which is an organizer called "Student Personal Organizer Assistant". With just a bit of an effort on their part, it will take care of all the messy details. It will take the form of a multimedia representation of an interactive study room where student manages most aspects of their daily lives. The tool will significantly increase their productivity levels and reduce the amount of irrelevance.